Well‐Aligned Hierarchical Graphene‐Based Electrodes for Pseudocapacitors with Outstanding Low‐Temperature Stability. Issue 10 (28th May 2019) - Kong, Jing; Xiong, Guoping; Bo, Zheng; Lu, Xinchao; Yi, Kexin; Kuang, Wenhao; Yang, Shiling; Yang, Huachao; Tian, Siyu; Yan, Jianhua; Cen, Kefa
Abstract: The relatively poor performance stability of pseudocapacitors over a wide temperature window (i. e. temperature stability), particularly at low temperatures, hinders their practical applications. Here, well‐aligned hierarchical pseudocapacitive electrodes are fabricated, featuring run‐through channels in a graphene network (GN) as ion‐buffering reservoirs, open inter‐sheet channels between vertical graphene nanosheets (VGNSs) for fast ion transport and MnO2 nanopetals on VGNSs for efficient interfacial pseudocapacitive reactions. With reduced ion diffusion length and charge‐transfer resistance as well as improved ion‐transport rate, the capacitance of pseudocapacitive electrodes decreases from 541 to 490 F g −1 at 1 A g −1 as the temperature drops from 25 to 0 °C, revealing a high capacitance retention of 90.7 %. Furthermore, the specific capacitance of a symmetric device based on the hierarchical electrodes at −30 °C maintains 80.8 % of the room‐temperature capacitance. Such outstanding temperature stability is comparable to the state‐of‐the‐art electric double‐layer capacitors. Importantly, 86.0 % of capacitance is retained after repeated heating and cooling at temperatures ranging from −30 to 60 °C for 5000 cycles. Asymmetric supercapacitors with the hierarchical architecture in the positive electrode exhibit stable performance over a wide temperature range. These results demonstrate the rationality of the electrode design for practical energy storage applications in harsh temperature environments. Abstract : Pseudocapacitors with outstanding low‐temperature stability : Well‐aligned hierarchical pseudocapacitive electrodes are designed and fabricated. Synergetic properties of the hierarchical microstructure facilitate fast ion transport and charge transfer processes, leading to outstanding low‐temperature stability of pseudocapacitors at −30 °C.